1989
DOI: 10.1111/j.1651-2227.1989.tb11129.x
|View full text |Cite
|
Sign up to set email alerts
|

Paralytic Ileus, a Serious Complication in Acute Diarrhoeal Disease among Infants in Developing Countries

Abstract: Intestinal hypomotility is a common late complication in infants with acute diarrhoeal disease in pakistan. Among the infants admitted to our gastrointestinal unit with a history of acute diarrhoea, 35% developed abdominal distension and 12% developed the full clinical picture of paralytic ileus. The infants with ileus were treated with decompression and total parenteral nutrition; in this group the mortality rate was 25%. We compared 30 infants who developed ileus (group A) with an age-matched control group o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

1991
1991
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 7 publications
0
5
1
Order By: Relevance
“…Paralytic ileus was found in 30(23.07%) children in our study population whereas it was reported significantly higher by Murtaza A, et al 15 They have reported that 35% infants with acute diarrhoea showed abdominal distention and 12% had full clinical picture of paralytic ileus in 1989. 15 Potassium deficiency alters functions of several organs and most prominently affects the cardiovascular and neurological systems, muscles and kidneys. 2 These effects ultimately determine the morbidity and mortality.…”
Section: Manifestationcontrasting
confidence: 51%
“…Paralytic ileus was found in 30(23.07%) children in our study population whereas it was reported significantly higher by Murtaza A, et al 15 They have reported that 35% infants with acute diarrhoea showed abdominal distention and 12% had full clinical picture of paralytic ileus in 1989. 15 Potassium deficiency alters functions of several organs and most prominently affects the cardiovascular and neurological systems, muscles and kidneys. 2 These effects ultimately determine the morbidity and mortality.…”
Section: Manifestationcontrasting
confidence: 51%
“…The effect of these drugs is mostly palliative as they do not improve rehydration, and the reduction in discharge can mask the underlying disease. They are contra-indicated because they can cause paralytic ileus [22] and blocking discharge while fluid continues to accumulate in the bowel can have lethal consequences. Furthermore, these drugs can negatively impact disease resolution by reducing the expulsion of bacteria.…”
Section: Current Treatment and New Therapeutic Opportunitiesmentioning
confidence: 99%
“…Abdominal distension and potentially fatal paralytic ileus have been reported in infants and young children treated with loperamide. [48][49][50] Toxic effects on the central nervous system have most commonly been observed in children <6 months of age. In conclusion, loperamide has no place in the routine management of diarrhea in children.…”
Section: Antimotility Drugsmentioning
confidence: 99%